The tachyon potential in open Neveu-Schwarz string field theory - Berkovits, Nathan [UNESP] (Editrice Compositori Bologna, 2000)
A classical action for open superstring field theory has been proposed which does not suffer from contact term problems. After generalizing this action to include the non-GSO projected states of the Neveu-Schwarz string, the pure tachyon contribution to the tachyon potential is explicitly computed. The potential has a minimum of V = 1/32g(2) which is 60% of the predicted exact minimum of V = 1/2 pi(2)g(2) from D-brane arguments.
Keywords: superstrings and heterotic strings; D-branes